Arab Spring in Egypt : revolution and beyond - Korany, Bahgat; El-Mahdi, Rabab (The American University in Cairo Press, 2012)
This study examines the background to the 2011 uprising in Egypt, the limits of authoritarian rule and the rise of new secular movements. It studies the group dynamics of workers, young people, and women, evaluates the role of the military, and considers the impact of regime change and future prospects for pan-Arabism.